Pengaruh Budaya Organisasi Dan Lingkungan Kerja Yang Berkelanjutan Terhadap Kepuasan Kerja Karyawan PT. Grahaprima Suksesmandiri Tbk. (GrahaTrans) - Nurkhaliza, Fitri; Lestari , Tri (CV Warnak Johanna Nusantara, 2025)
One of the indicators that support Human Resource Management is the level of employee job satisfaction. There are many factors that can influence employee job satisfaction, including organizational culture and a sustainable work environment. This study aims to analyze the influence of organizational culture (X1) and a sustainable work environment (X2) on employee job satisfaction (Y) at PT Grahaprima Suksesmandiri Tbk (GrahaTrans). This research uses a quantitative approach with a causal associative research design. The data collection technique was carried out by distributing questionnaires to eighty-six respondents, and data analysis was conducted using IBM Statistical Package for the Social Sciences (SPSS) version 23. The results of the study show that organizational culture has a positive and significant effect on employee job satisfaction with a t-value of 3.987 and a significance level of 0.000. A sustainable work environment also has a positive and significant effect on job satisfaction with a t-value of 4.161 and a significance level of 0.000. Simultaneously, both of these variables have a significant influence on employee job satisfaction with an F-value of 51.181 and a significance level of 0.000. These findings indicate that improving organizational culture and creating a healthy and sustainable work environment are very important to increase overall employee job satisfaction.